Haematological indices of Wistar rats fed dehulled African yam bean (stenostylis stenocarpa) soaked in acidic and alkaline media (2015)
A total of thirty Wistar rats weighing 40±50g were randomly allocated to three dietary treatments in a completely randomized block design to investigate the haematological indices of Wistar rats fed dehulled African yam bean (Sphenostylis stenocarpa) soaked in acidic and alkaline media. Three diets were formulated to contain dehulled AYB- (TI), dehulled AYB soaked ogi liquor (acidic medium)- (T3) and dehulled AYB soaked in wood ash (alkaline solution)-(T3). The experiment lasted for 28days. Two rats per treatment were sacrificed by cervical decapitation, Red Blood Cell (RBC), lymphocyte AST and creatinine were not affected by dietary treatments while Packed Cell Volume, Haemoglobin, White Blood Cell, Neutrophils, Monocytes, Basophil, Platelets, total protein, albumin, globulin and ALT were significantly affected (P>0.05) by dietary treatments. Rats on T3 had the highest haemoglobin value (15.6g/dl) and PCV (48.0%). Rats on T2 and TI had the highest value of monocyte (2.00%) and basophil (2.00%) However, values of PCV and Haemoglobin followed similar pattern. In conclusion dehulled African yam bean seeds soaked in ogi liquor (acidic medium) and wood ash (alkaline medium) can be fed to rats without having adverse effects on haematological indices of the rats.